A study of disseminated intravascular coagulation in acute leukemia reveals markedly elevated D‐dimer levels are a sensitive indicator of acute promyelocytic leukemia. (19th April 2017) - Shahmarvand, N.; Oak, J. S.; Cascio, M. J.; Alcasid, M.; Goodman, E.; Medeiros, B. C.; Arber, D. A.; Zehnder, J. L.; Ohgami, R. S.
Summary: Introduction: While the presence of disseminated intravascular coagulation (DIC) has been implicated in worse clinical outcome in acute leukemia, the relationship between different subtypes of acute leukemia and the clinicopathologic features of DIC has not been systematically well studied. Methods: In this study, we retrospectively reviewed 149 cases of newly diagnosed acute leukemia and assessed the utility of evaluating red blood cell morphologic features, and coagulation parameters in determining the presence of DIC as well as differentiating subtypes of acute leukemia. Results: Review of our cohort demonstrates a novel finding, that elevated D‐dimer concentrations ≥19 000 ng/mL fibrinogen equivalent units (FEU) are a sensitive diagnostic indicator of acute promyelocytic leukemia (APL) with moderate specificity, sensitivity 96%, specificity 92% in acute leukemia subtyping. Similar to other studies, APL showed an increased incidence of DIC ( P < 0.01) compared to other subtypes of acute leukemia. Surprisingly, the presence of schistocytes on the peripheral blood smear was not a statistically significant indicator of DIC, sensitivity of 36% and specificity of 89%. Finally, the presence of DIC was not a significant indicator of poorer prognosis amongst all patients with AML. Conclusion: Overall we identify elevated D‐dimer concentrations ≥19 000 ng/mL FEU are a sensitive indicator of acute promyelocytic leukemia (APL), with a sensitivity of 96% and specificity of 92% in the subtyping of acute leukemias, and that the presence of schistocytes in peripheral blood smears is not a diagnostically sensitive screening test for DIC with a sensitivity of 36%.